Dipeptidyl Peptidase‐4 Is a Pro‐Recovery Mediator During Acute Hepatotoxic Damage and Mirrors Severe Shifts in Kupffer Cells. Issue 9 (7th September 2018) - Duarte, Nádia; Coelho, Inês; Holovanchuk, Denys; Inês Almeida, Joana; Penha‐Gonçalves, Carlos; Paula Macedo, Maria
Abstract : Dipeptidyl peptidase‐4 (DPP‐4 or clusters of differentiation [CD]26) is a multifunctional molecule with established roles in metabolism. Pharmacologic inhibition of DPP‐4 is widely used to improve glycemic control through regulation of the incretin effect. Colaterally, CD26/DPP‐4 inhibition appears to be beneficial in many inflammatory conditions, namely in delaying progression of liver pathology. Nevertheless, the exact implications of CD26/DPP‐4 enzymatic activity in liver dysfunction remain unclear. In this work, we investigated the involvement of CD26/DPP‐4 in experimental mouse models of induced hepatocyte damage that severely impact Kupffer cell (KC) populations. Liver dysfunction was evaluated in CD26 knockout (KO) and B6 wild‐type mice during acute liver damage induced by acetaminophen, chronic liver damage induced by carbon tetrachloride, and KC‐depleting treatment with clodronate‐loaded liposomes. We found that necrosis resolution after hepatotoxic injury was delayed in CD26KO mice and in B6 mice treated with the CD26/DPP‐4 inhibitor sitagliptin, suggesting that DPP‐4 enzymatic activity plays a role in recovering from acute liver damage. Interestingly, the severe KC population reduction in acute and chronic liver injury was concomitant with increased CD26/DPP‐4 serum levels. Remarkably, both chronic liver damage and noninflammatory depletion of KCs by clodronate liposomes were marked by oscillation in CD26/DPP‐4 serum activity that mirrored the kinetics of liver KC depletion/recovery. Conclusion :CD26/DPP‐4 enzymatic activity contributes to necrosis resolution during recovery from acute liver injury. Serum CD26/DPP‐4 is elevated when severe perturbations are imposed on KC populations, regardless of patent liver damage. We propose that serum CD26/DPP‐4 is a potential systemic surrogate marker of severe impairments in the KC population imposed by clinical and subclinical liver conditions.